The participatory budget in public investment projects in the Huánuco Regional Government, 2012-2014 - Argüezo-Lozano, Alicia N. (2019)
The study carried out corresponds to a quantitative research in a sample of 29 projects of Public Investment in the sectors of education and health of the Regional Government Huánuco the years 2012-2014. Objective: To determine the condition of the Participatory Budget in the Public Investment Projects in the sectors of education and health in the Huánuco Regional Government, 2012-2014. Methods: the general method was the scientific and as a specific, descriptive method. The research was basic, descriptive level and descriptive (non-experimental) design. The population consisted of 29 analyzed projects. The conclusion of this research: It has been determined that the Participatory Budget in Public Investment Projects in the Regional Government 2012-2014, in the Education Sector 46.67% is found as projects executed. While in the Health Sector 35.71% is in the condition of executed projects.